EFEKTIFITAS TERAPI ABDOMINAL STRETCHING EXERCISE DENGAN SEMANGKA TERHADAP DISMENORHOE - Harmina, Harmina; hasnah, hasnah (Universitas Islam Negeri Alauddin Makassar, 2017)
Introduction: Dysmenorrhea is lower abdominal pain that is felt just before or during menstruation. This Diamenorhea can disrupt a person's activity and can indirectly affect the productivity and quality of life. Dismenorhea can be resolved with non-pharmacological therapies, one of that is with Abdominal Stretching Exercise therapy with Watermelon. Objective: This study aimed to determine the effectiveness of therapy abdominal stretching exercise with watermelon against Dismenorhea on Nursing student UIN Alauddin Makassar. Methods: This study was conducted in February 2016 by the method of the research a Quasi-Experimental Non-Randomized Control group pretest-posttest. Analysis of data using statistical test of Wilcoxon t-test. Respondents were 20 people, ten people as intervention group and ten people as control group and collected data by purposive sampling method. Results : based on test results obtained statistical p value = 0.004, which means that there are significant differences Dismenorhea pre-test to post-test after abdominal stretching exercise therapy with watermelon. Discussion: Exercise is proven to increase endorphin levels four to five times in the blood, where increasing endorphin proved closely associated with a decrease in pain, especially pain Dismenorhea. Watermelon itself contains a lot of water so that it can function as a diuretic, which have a diuretic effect that relaxes the muscle menstrual cramps become limp. Conclusion: It can be concluded that treatment with watermelon abdominal stretching exercise effective against Dismenorhea and this therapy could be an alternative for someone who has Dismenorhea.